2018
DOI: 10.4013/fsu.2018.191.06
|View full text |Cite
|
Sign up to set email alerts
|

Mental time travel and the philosophy of memory

Abstract: The idea that episodic memory is a form of mental time travel has played an important role in the development of memory research in the last couple of decades. Despite its growing importance in psychology, philosophers have only begun to develop an interest in philosophical questions pertaining to the relationship between memory and mental time travel. Thus, this paper proposes a more systematic discussion of the relationship between memory and mental time travel from the point of view of philosophy. I start b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…In developing their account, Hutto and Peeters appeal to three distinct bodies of theory, invoking treatments of remembering as, first, extended and embodied (Clark and Chalmers, 1998;Sutton and Williamson, 2014), second, reconstructive, simulative, or imaginative (Perrin and Michaelian, 2017;Sant'Anna, 2018;Michaelian et al, 201x), and, third, nonrepresentational or contentless (Loader, 2013;De Brigard, 2014). 3 The aspects of remembering on which the first two of these focus would seem, on the face of it, to pair naturally with an account of remembering as involving the retrieval of stored content, but Hutto and Peeters argue that they are in fact best accommodated by an enactivist version of the sort of contentless account suggested by the third.…”
Section: Radical Enactivism Meets the Philosophy Of Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…In developing their account, Hutto and Peeters appeal to three distinct bodies of theory, invoking treatments of remembering as, first, extended and embodied (Clark and Chalmers, 1998;Sutton and Williamson, 2014), second, reconstructive, simulative, or imaginative (Perrin and Michaelian, 2017;Sant'Anna, 2018;Michaelian et al, 201x), and, third, nonrepresentational or contentless (Loader, 2013;De Brigard, 2014). 3 The aspects of remembering on which the first two of these focus would seem, on the face of it, to pair naturally with an account of remembering as involving the retrieval of stored content, but Hutto and Peeters argue that they are in fact best accommodated by an enactivist version of the sort of contentless account suggested by the third.…”
Section: Radical Enactivism Meets the Philosophy Of Memorymentioning
confidence: 99%
“…Klein (2015), too, though he singles episodic memory out as having a special status (see section 5), posits a fundamental similarity between episodic and semantic memory, arguing that the difference between them is purely phenomenological; this similarly suggests that, if we are entitled to describe episodic memory as a form of imagination, we are likewise entitled to describe semantic memory as a form of imagination. Of course, the availability of these views does not settle the matter, and one might reinforce the worry by noting that, while the relationship between episodic memory and imagination has been established by research on episodic memory as a form of mental time travel tightly linked episodic future thought (Perrin and Michaelian, 2017;Sant'Anna, 2018), no similar link between semantic memory and an analogous future-oriented capacity has been established. In response, we point out that, while most research on memory as a form of mental time travel so far has focused on episodic memory and episodic future thought, there is increasing emphasis on the role of semantic memory in future-oriented mental time travel (Irish, 2016) and indeed on properly semantic forms of futureoriented thought (Klein et al, 2002;Szpunar et al, 2016).…”
Section: Semantic Memory Without Contentmentioning
confidence: 99%
“…The continuism-discontinuism debate is multifaceted, and there are a number of other issues that this chapter might have broached (see Perrin & Michaelian, 2017;Sant'Anna, 2018; for a recent review from a psychological perspective, see Addis, 2018). Before concluding, we briefly explore just one of these: the implications of continuism and discontinuism for the possibility of future-oriented confabulation.…”
Section: Immunity To Error Through Misidentification In Episodic Memomentioning
confidence: 98%
“… 1 I should note here that, in more recent works, Tulving has changed his understanding of what episodic memory is, focusing now on its phenomenological dimension (see Tulving, 2002 , 2005 ). According to him, episodic memory involves a unique kind of consciousness—what he calls autonoetic consciousness —which allows subject to “mentally travel” in subjective time, such that they can “re-live” or “re-experience” the past events (see also Klein, 2015 ; Perrin and Michaelian, 2017 ; Sant'Anna, Forthcoming ). This new definition has led Tulving to claim that episodic memory is uniquely human, as the capacity to mentally travel in subjective time requires other cognitive capacities that are only present in humans.…”
mentioning
confidence: 99%
“…Developmental and memory impairment studies have also provided further support for this idea, as it has been found that children develop the capacity to remember the past and to imagine the future arise at approximately the same time (Suddendorf and Busby, 2005 ; Atance, 2008 ; Fivush, 2011 ), and that deficits in memory incur similar deficits in the ability to think about future scenarios (Klein et al, 2002 ; Rosenbaum et al, 2005 ; Hassabis et al, 2007 ). See also Perrin and Michaelian ( 2017 ) and Sant'Anna ( Forthcoming ) for related discussions from a philosophical perspective, and Debus ( 2014 ) for a critical view of the idea that episodic memory is a form of mental time travel.…”
mentioning
confidence: 99%